Neuro-Organizational Culture A new approach to understanding human behavior and interaction in the workplace - Reisyan, Garo D. (Springer International Publishing : Imprint: Springer, 2016)
This book introduces a new concept on organizational culture, called 'Neuro-Organizational Culture', or 'Neuroculture'; a concept that is based on the most recent neuroscientific knowledge. The book describes a new approach to understanding human behavior and interaction in the workplace, replacing the old concept of organizational culture by one that takes into account humans' perceiving, feeling, thinking, and acting. Taking advantage of the substantial progress that has been made in neuroscientific research, the book combines experiences gained from organizational culture in the past 30 years with the latest findings from brain and emotion research, as well as with important insights from sociology and psychology. The book explains the three building blocks of Neuroculture: Reflexivity, Notions, and Emotions. Neuroculture consistently conceptualizes the culture of groups and individuals consistently under one roof, which allows for a better explanation of individual deviations. It provides a structural framework and an inventory along with proven methods and templates to analyze, continuously foster and actively change organizational culture. In addition, it outlines global megatrends in order to define cultural requisites that promote sustainable success of organizations in the 21st century.